(untitled) (Engrami, 2022)
Introduction: Recent studies about Mindful Attention and Awareness elucidated its potential role in affective difficulties and behavioral regulation, but authors call for further investigation of potential underlying mechanisms. Research goal: The current study was conducted in order to examine the preliminary psychometric properties of the Serbian Mindful Attention and Awareness scale, its relationship with positive psychological constructs, along with its mediating role in the relationships of Depressiveness as a trait, with behavioral Activation, and Avoidance. Method: A cross-sectional research was conducted on a sample of 504 students of different levels and courses of education in the Serbian speaking area. Results: Serbian version of Mindful Attention and Awareness scale demonstrated high reliability (α=0.83) and a single factor solution that was found to be the most adequate. Significant correlations with theoretically related positive psychological constructs such as Gratitude (r=0.12, p<0.001), Self-compassion (r=0.46, p<0.001) and its components such Self-kindness (r=0.21, p<0.001), Over identification (r=-0.47, p<0.001) and Mindfulness (r=0.29, p<0.001) were found. It was also the case for distress components such as Depressiveness (r=-0.41, p<0.001), Anxiety (r=-0.46, p<0.001) and Stress (r=-0.50, p<0.001), as well as for Behavioral activation for depression (r=0.46, p<0.01) and its components Activation (r=0.34, p<0.01) and Avoidance (r=-0.35, p<0.01). Additionally, it was found that Mindful Attention and Awareness significantly mediates the relationship between Depressiveness and Activation as well as in the case of Depressiveness and Avoidance. Conclusion: Along with the study limitations, the mindfulness enhancing effect was discussed in accordance with its potentially mitigating effects on unpleasant automatic states and regulation of behavior patterns, so that it might contribute to the development of value-guided behaviors. Key words: Mindful Attention and Awareness; Depressiveness; Behavioral activation; Avoidance